Cross-sectional study measuring the level and relationship of awareness, attitude and willingness to use HIV pre-exposure prophylaxis in Davao City, Philippines - Von Jay Maico Gillado Gabucan (BMJ Open)
Objectives To improve on the implementation and uses of HIV pre-exposure prophylaxis (PrEP) programmes, factors affecting HIV PrEP willingness must be investigated. This study aims to determine not only the willingness to use HIV PrEP but also to establish whether awareness and attitude affect this.Design This study used a cross-sectional survey research design to examine the awareness, attitude and willingness to use HIV PrEP in Davao City. The survey was adapted from multiple studies and was validated and pilot tested. Statistical analysis included descriptive and inferential statistics like correlation, linear regression and structural modelling.Settings This research was conducted in Davao City, Philippines. This is one of the regions in the country with a high HIV incidence. The survey was conducted from March to June 2024.Participants Participants were at least 18 years of age, currently living in Davao City and a permanent resident of the city.Results A total of 258 respondents were gathered in this study, of which 53.10% of all respondents were fully aware of HIV PrEP, while 27.13% were partially aware. The study found the mean attitude and willingness to be 4.21±0.686 and 4.08±0.685, respectively. There was a significant difference in the awareness when grouped according to identity category (X2=24.428; p value=0.002) and highest education attained (X2=15.919; p value=0.044). Being fully aware positively affected willingness to use HIV PrEP by indirectly contributing positively to attitude towards HIV PrEP (β=0.180; p value=0.012).Conclusion Generally, the awareness, attitude and willingness to use HIV PrEP is high. However, some respondents are hesitant to use HIV PrEP if it is not a hundred percent effective and unable to adhere to it. The results imply a need for action programmes involving various multidisciplinary stakeholders to ensure that the community possesses full awareness, positive attitudes and increased willingness to use HIV PrEP.